Studi Analisis Tentang Resiliensi Terkait Harga Diri dan Sosial Kognitif pada Remaja Panti Asuhan Anak Harapan Samarinda - Rusni Masnina (Jurnal Ilmu Kesehatan, 2017)
Background: Adolescence is the period of life of a child who develops into adulthood. Adolescence is often characterized by transitions and changes. Facing his life in the future, adolescents need to have great confidence and hope in order to be able to rise from the difficult conditions and negative emotional experience experienced. For adolescents who live in the orphanage, not having a family or not living with their parents necessarily need to form a strong personality in terms of self-esteem, social cognitive and self-resilience to become adult human beings who are useful and responsible both for themselves and for the people in later.Objectives: This study was aimed to analyze "Resilience related to Self-Esteem and Social Cognitive among adolescents at Panti Asuhan Anak Harapan Samarinda"Methods: The design of this study was descriptive cross-sectional. Population in this research was adolescent amounted to 90 people with the sample of 73 respondents taken using purposive sampling method, where this research use inclusion and exclusion criteria. The statistical analysis used in this research was chi-square statistic testResults: Based on the results of the study, there was a significant relationship between self-esteem and resilience in adolescent (p value = 0,016 <α = 0,05), as well as there was significant relationship between social cognitive and resilience (p value: 0.000 <α 0.05)Conclusion: Majority of adolescent who have better resilience was due to better self-esteem and social cognitive. Beside influenced by these inner factors they were also supported from people around especially the caregivers at the orphanage.